Hubungan Harga Diri dan Iklim Sekolah dengan Perilaku Bullying di SMA Swasta Mamiyai Al-Ittyhadiyah Medan - Ade Kurnia Sari; Abdul Munir; Hasanuddin Hasanuddin (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to determine the relationship between self-esteem and school climate with bullying behavior at private high school Mamiyai Al-Ittyhadiyah Medan. This type of research is quantitative research with correlational method. The subjects in this study were students at Mamiyai Al-Ittihadiyah Medan with the results showing that: (1) There was a significant negative relationship between self-esteem and bullying behavior as indicated by the coefficient rx1y = -0.525; p = 0.001 p <0.05, the results show that self-esteem has a predictive power towards bullying behavior of 27.5%. (2) There is a significant negative relationship between school climate and bullying behavior in Mamiyai Al-Ittihadiyah Medan as indicated by rx2y = -0.546 ; p = 0.000 p <0.05, the result is that the school climate has a predictive power to the emergence of bullying behavior by 29.8%. (3) There is a significant relationship between self-esteem and school climate with bullying behavior as indicated by the coefficient F=12.039 R=-0.560 while R2=0.313 with p=0.000 P<0.05. Taken together, self-esteem and school climate have predictive power to the emergence of bullying behavior by 30.3%. From this result, it is known that there are still 69.7% contributions from other factors or variables to the formation of bullying behavior. From the results of this study, the proposed hypothesis is accepted.